Failure of unravelling theory? A natural field experiment on voluntary quality disclosure - Tom Lane; Minghai Zhou (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2021)
This paper presents a simple adaptive model of demand adjustment in cooperative games, and analyzes this model in weighted majority games. In the model, a randomly chosen player sets his demand to the highest possible value subject to the demands of other coalitions members being satisfied. This basic process converges to the aspiration set. By introducing some perturbations into the process, we show that the set of separating aspirations, i.e. demand vectors in which no player is indispensable in order for other players to achieve their demands, is the one most resistant to mutations. We then apply the process to weighted majority games. We show that in symmetric majority games and in apex games the unique separating aspiration is the unique stochastically stable one.
Keywords: C72; D82; D83; J23; 330; Voluntary Disclosure; Unravelling; Labour Market; Field Experiment